Physiology of Highly Radioresistant Escherichia coli After Experimental Evolution for 100 Cycles of Selection - Bruckbauer, Steven T.; Martin, Joel; Minkoff, Benjamin B.; Veling, Mike T.; Lancaster, Illissa; Liu, Jessica; Trimarco, Joseph D.; Bushnell, Brian; Lipzen, Anna; Wood, Elizabeth A.; Sussman, Michael R.; Pennacchio, Christa; et al. (Frontiers in Microbiology, 2020)
Ionizing radiation (IR) is lethal to most organisms at high doses, damaging every cellular macromolecule via induction of reactive oxygen species (ROS). Utilizing experimental evolution and continuing previous work, we have generated the most IR-resistant Escherichia coli populations developed to date. After 100 cycles of selection, the dose required to kill 99% the four replicate populations (IR9-100, IR10-100, IR11-100, and IR12-100) has increased from 750 Gy to approximately 3,000 Gy. Fitness trade-offs, specialization, and clonal interference are evident. Long-lived competing sub-populations are present in three of the four lineages. In IR9, one lineage accumulates the heme precursor, porphyrin, leading to generation of yellow-brown colonies. Major genomic alterations are present. IR9 and IR10 exhibit major deletions and/or duplications proximal to the chromosome replication terminus. Contributions to IR resistance have expanded beyond the alterations in DNA repair systems documented previously. Variants of proteins involved in ATP synthesis (AtpA), iron-sulfur cluster biogenesis (SufD) and cadaverine synthesis (CadA) each contribute to IR resistance in IR9-100. Major genomic and physiological changes are emerging. An isolate from IR10 exhibits protein protection from ROS similar to the extremely radiation resistant bacterium Deinococcus radiodurans, without evident changes in cellular metal homeostasis. Selection is continuing with no limit to IR resistance in evidence as our E. coli populations approach levels of IR resistance typical of D. radiodurans.